Cerebrospinal fluid neurofilament light concentration predicts brain atrophy and cognition in Alzheimer's disease. Issue 1 (27th February 2020) - Dhiman, Kunal; Gupta, Veer Bala; Villemagne, Victor L.; Eratne, Dhamidhu; Graham, Petra L.; Fowler, Christopher; Bourgeat, Pierrick; Li, Qiao‐Xin; Collins, Steven; Bush, Ashley I.; Rowe, Christopher C.; Masters, Colin L.; et al.
Abstract: Introduction: This study assessed the utility of cerebrospinal fluid (CSF) neurofilament light (NfL) in Alzheimer's disease (AD) diagnosis, its association with amyloid and tau pathology, as well as its potential to predict brain atrophy, cognition, and amyloid accumulation. Methods: CSF NfL concentration was measured in 221 participants from the Australian Imaging, Biomarkers & Lifestyle Flagship Study of Ageing (AIBL). Results: CSF NfL levels as well as NfL/amyloid β (Aβ42) were significantly elevated in AD compared to healthy controls (HC; P < .001), and in mild cognitive impairment (MCI) compared to HC ( P = .008 NfL; P < .001 NfL/Aβ42). CSF NfL and NfL/Aβ42 differentiated AD from HC with an area under the receiver operating characteristic (ROC) curve (AUC) of 0.84 and 0.90, respectively. CSF NfL and NfL/Aβ42 predicted cortical amyloid load, brain atrophy, and cognition. Discussion: CSF NfL is a biomarker of neurodegeneration, correlating with cognitive impairment and brain neuropathology.